9(2n-1)=(8n+4)+3

Simple and best practice solution for 9(2n-1)=(8n+4)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2n-1)=(8n+4)+3 equation:


Simplifying
9(2n + -1) = (8n + 4) + 3

Reorder the terms:
9(-1 + 2n) = (8n + 4) + 3
(-1 * 9 + 2n * 9) = (8n + 4) + 3
(-9 + 18n) = (8n + 4) + 3

Reorder the terms:
-9 + 18n = (4 + 8n) + 3

Remove parenthesis around (4 + 8n)
-9 + 18n = 4 + 8n + 3

Reorder the terms:
-9 + 18n = 4 + 3 + 8n

Combine like terms: 4 + 3 = 7
-9 + 18n = 7 + 8n

Solving
-9 + 18n = 7 + 8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-8n' to each side of the equation.
-9 + 18n + -8n = 7 + 8n + -8n

Combine like terms: 18n + -8n = 10n
-9 + 10n = 7 + 8n + -8n

Combine like terms: 8n + -8n = 0
-9 + 10n = 7 + 0
-9 + 10n = 7

Add '9' to each side of the equation.
-9 + 9 + 10n = 7 + 9

Combine like terms: -9 + 9 = 0
0 + 10n = 7 + 9
10n = 7 + 9

Combine like terms: 7 + 9 = 16
10n = 16

Divide each side by '10'.
n = 1.6

Simplifying
n = 1.6

See similar equations:

| 2(x-1)=24 | | 93=-6x+3(-2x-13) | | 8x-12+7=-3 | | 3x^2+30x-4=0 | | 4x+11=10x-7 | | z+5=-5 | | 4(3x-5)+x=z | | 11y-12=6y+8 | | 6y+4=2y+20 | | 5xa+7=c+a | | 4(3x-5)+x= | | 10x+5(z-12)=0 | | -3x-10=-2x+4 | | 0.6(j-2)=0.3l | | 20+x=2(20-2x) | | 14-d=45 | | x+2x+2x-30=5400 | | 8-n-3n=6 | | -6x+2y=5 | | 6x-2(-6x+3)=120 | | 2x+20=-3x+50 | | 4(x-3)+7=-3 | | 7x+2(3x+7)=144 | | 6x^2+9x-4=38 | | ax^3+bx-5=0 | | D+8=-7 | | -4(n-b)=12 | | 9(n+6)-5(2+2n)=-8n+5n | | 5(x+4)+14=59 | | 21=3(c-9) | | 6x-2(-6+3)=120 | | 3a+3b+3c=3b |

Equations solver categories